IMPLEMENTATION OF THE PROBLEM-BASED LEARNING METHOD TO IMPROVE THE UNDERSTANDING OF GRADE X GPI STUDENTS AT SMK NEGERI 4 MEULABOH ON MORALS IN ISLAM - Hermiyanti (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students' character and morals. One key aspect is moral education, which aims to instill Islamic ethical and moral values in daily life. However, around 60% of students at SMK Negeri 4 Meulaboh struggle to grasp the concept of Islamic morals. This issue is reflected in their low minimum competency scores (KKM), primarily due to the monotonous and unengaging lecture-based teaching method commonly used by teachers, which quickly leads to boredom. To address this problem, an alternative approach is needed to ensure students can effectively absorb moral education. One potential solution is the implementation of the Problem-Based Learning (PBL) method. This study aims to analyze the effectiveness of PBL in improving students' understanding of moral education in Islam. The research follows a Classroom Action Research (CAR) methodology, conducted in two cycles.